Attitudes to and Understanding of Placebo Use: A Cross- Sectional Exploratory Study in a Malaysian Hospital - Amanda Villiers Tuthill; Tay Zhuo Han; Chang Xian Chai; Ai Wen Chai; Chun Yiing Wong; Karen Morgan (University Library System, University of Pittsburgh, 2016)
Background: This study explored doctors' understanding of 'placebo', mechanisms of action, perceptions about effectiveness and concerns about use in a Malaysian teaching hospital. Methods: A survey questionnaire. Results: Respondents were 76 doctors (response rate: 55%): 52% were female, mean age was 32 years, and 61% were physicians/medical officers. Most (66.2%) never used a placebo. The main reason for use of placebos was for a possible psychological effect. Placebo use was considered unacceptable due to endangering of doctor-patient trust (59.2%) or patient deception (47.4%). Conclusion: Developing specific and professional standards and guidance on placebo use could help doctors to leverage the benefits of placebo use without endangering the doctor-patient relationship.